Determination of education level, competence and work environment in the intervening motivation on the performance of Health Centre Health Workers in Karimun District - Indra, Indra; Wibisono, Chabulullah; Indrawan, Mohamad Gita (Goodwood Publishing, 2024)
Purpose: This study aimed to examine the influence of education level, competence, and work environment on the performance of Community Health Centre (Puskesmas) health workers in Karimun Regency, with work motivation analyzed as an intervening variable. Research Methodology: A quantitative approach was used with 139 health workers selected through the Slovin formula from a population of 631 individuals. Primary data were collected using questionnaires, supported by observations and interviews, while secondary data were obtained from official records. Partial Least Squares (PLS) analysis was employed with SmartPLS to test validity, reliability, structural relationships, and mediation effects. Results: The findings indicate that education level and work environment significantly influence both motivation and performance, while competence shows no significant direct effect on either motivation or performance. Motivation significantly enhances performance. Mediation testing revealed that motivation did not mediate the effect of education level and competence on performance but partially mediated the influence of the work environment on performance. Conclusions: The study concludes that while higher education and better work environments improve motivation and performance, competence development programs remain insufficient and have not significantly impacted the outcomes. Creating supportive work environments and fulfilling health workers’ basic needs are crucial for sustaining performance. Limitations: This study was limited to one district and relied on self-reported measures, which may affect generalizability and accuracy. Contribution: This study contributes to public sector human resource management by demonstrating the mediating role of motivation and highlighting the importance of education and workplace conditions in strengthening health workers’ performance.